Productivity and agronomic characteristics of sugarcane under different tillage systems - Moraes, E. R.; Bernardes, R. F. B.; Domingues, L. A. S.; Lana, R. M. Q. (Scientific Electronic Archives, 2017)
Sugarcane production has increased in recent years mainly because of the demand for ethanol. Soil preparation in areas where sugarcane has not been planted yet can increase productivity by improving physical and chemical characteristics. The objective of this study was to evaluate the effect of soil tillage on agronomic traits and productivity of sugarcane. The experiment was conducted in the municipality of Goianésia (GO) on a Red-Yellow Latosol of medium texture using the CTC-2 variety. The experimental design was randomized blocks with six treatments and four replications. The treatments were: T1) desiccation + moldboard plow + harrow, T2) moldboard plow + harrow, T3) harrow + moldboard plow + harrow, T4) no-till, T5) subsoiler, and T6) harrow + disc plow + harrow. The number, diameter, height and productivity of stalks were evaluated. The treatment which resulted in the highest number of stalks was harrow + moldboard plow + harrow; however, this treatment was differed only from the treatment with moldboard plow + harrow. The seedbed preparation with desiccation + moldboard plow + harrow and also harrow + disk plow + harrow provided the highest yield of sugarcane stalks. The no-till treatment proved to be a viable alternative, since it did not differ in productivity from treatments that provided the highest yields. It is a more economical form of cultivation when compared to the other treatments studied in this work.